2020
DOI: 10.1038/s41598-020-70742-3
|View full text |Cite
|
Sign up to set email alerts
|

Six to 12-year outcomes of magnetic sphincter augmentation for gastroesophageal reflux disease

Abstract: The magnetic sphincter augmentation (MSA) device has been proven safe and effective in controlling typical reflux symptoms and esophageal acid exposure for up to 6-year follow-up. Longer term outcomes have not been reported yet. A prospectively maintained database was reviewed to assess long-term safety and efficacy of the laparoscopic MSA procedure at a single referral center. Gastro-Esophageal Reflux Disease-Health Related Quality of Life (GERD-HRQL), use of proton-pump inhibitors (PPI), and esophageal acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 35 publications
3
35
1
1
Order By: Relevance
“…In 2020, Bonavina, in Ferrari et al . 14 published on their single institution experience with MSA in 335 patients, beginning in 2007. This publication embodies the learnings over 12 years of implanting MSA.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Bonavina, in Ferrari et al . 14 published on their single institution experience with MSA in 335 patients, beginning in 2007. This publication embodies the learnings over 12 years of implanting MSA.…”
Section: Discussionmentioning
confidence: 99%
“…Die MSA führt sowohl zu einer signifikanten Verlängerung des gesamten als auch des intraabdominellen unteren Ösophagussphinkters sowie zu einer signifikanten Erhöhung des IRP (integrated relaxation pressure) [18]. Rezent veröffentlichte Langzeitergebnisse (mediane Nachbeobachtungszeit 9 Jahre) haben die Kurzzeitergebnisse bestätigt: signifikante Lebensqualitätsverbesserung (GERD-HRQL19,9 auf 4,1; p = 0,001), PPI-Freiheit bei 79 % der Patienten und Normalisierung der Säureexposition im distalen Ösophagus (pH < 4 von 9,6 auf 4,1 %; p < 0,001) bei 89 % der Patienten nach MSA [19]. Im randomisierten Vergleich mit optimierter PPI-Einnahme zeigt sich ein statistisch signifikanter Vorteil für die MSA bez.…”
Section: Magnetische Sphinkteraugmentation (Msa)unclassified
“…Magnetic sphincter augmentation (MSA) is a novel laparoscopic procedure designed to augment the barrier function of the lower esophageal sphincter (LES). It has been shown that MSA can reduce GERD symptoms and improve patients' quality of life up to 12 years of follow‐up 3 …”
Section: Introductionmentioning
confidence: 99%